A cyanobacteria-derived intermolecular salt bridge stabilizes photosynthetic NDH-1 and prevents oxidative stress - Mei Zheng; Yuanyuan Jiang; Zhaoxing Ran; Shengjun Liang; Tingting Xiao; Xiafei Li; Weimin Ma (Communications Biology)
Abstract Throughout evolution, addition of numerous cyanobacteria-derived subunits to the photosynthetic NDH-1 complex stabilizes the complex and facilitates cyclic electron transfer around photosystem I (PSI CET), a critical antioxidant mechanism for efficient photosynthesis, but its stabilization mechanism remains elusive. Here, a cyanobacteria-derived intermolecular salt bridge is found to form between the two conserved subunits, NdhF1 and NdhD1. Its disruption destabilizes photosynthetic NDH-1 and impairs PSI CET, resulting in the production of more reactive oxygen species under high light conditions. The salt bridge and transmembrane helix 16, both situated at the C-terminus of NdhF1, collaboratively secure the linkage between NdhD1 and NdhB, akin to a cramping mechanism. The linkage is also stabilized by cyanobacteria-derived NdhP and NdhQ subunits, but their stabilization mechanisms are distinctly different. Collectively, to the best of our knowledge, this is the first study to unveil the stabilization mechanism of photosynthetic NDH-1 by incorporating photosynthetic components into its conserved subunits during evolution.